Experience of using psychological support for 6th year medical university students in conditions of high stress levels and reduced quality of life indicators - O.O. Khanyukov; V.Yu. Krotova; S.S. Panina; V.V. Khramtsova; K.Yu. Yegorov; O.S. Shchukina (Medičnì Perspektivi, 2025)
Constant and excessive stress leads to psychological disorders in medical students, especially in ones of senior years of study. This creates problems with motivation to acquire knowledge, concentration, memorization of necessary information, an increase in the number of errors, the result of which can be a decrease in academic performance of a student of higher medical education. Student youth is the future of our country, therefore it is important to study the state of physical and psychological health of students and make every effort to improve their quality of life, especially in conditions of constant stress. The purpose of the study was to assess the level of anxiety and depression in students of the 6th year of a higher medical education institution, their quality of life, vitality and resilience, as well as to determine the directions of effective psychological support in conditions of constant stress. To achieve the goal, the quality of life was determined according to the SF-36 scale, the level of anxiety and depression – according to the HADS scale, the level of vitality - according to the S. Maddi "Test of Vitality" and resilience – according to the CD-RISC-10 technique. 61 students of the 6th year of the Dnipro State Medical University took part in the primary study. Among them, 42 students took part in psychological support during a 2-month cycle. According to the results of the study, it was found that the reduced level of quality of life was in mental health – MH=59.6±2.46), social functioning – SF=58.4±2.5), vital activity – V=53.7±2.46. According to the HADS anxiety and depression scales, it was determined that subclinical anxiety and depression syndrome occurred in 9 (14.8%) and 7 (11.4%) students, respectively, and high anxiety and depression scores (11 points and above) were diagnosed in 14 (23%) and 9 (14.8%) people. The integral index of vitality among students exceeded the average level in 25 (41.0% (81.7±1.0 points)) of students, its high indicators were in 21 (34.4% (100.8±1.59 points), and low in 15 (24.6% (57.3±2.64 points)) students, respectively. The level of resilience in all examined students was within 29.7±1.15, which is an average indicator. Psychological support provided to students had a positive effect on role-based physical functioning, as an indicator of quality of life, on the reduction of psychological tension, which improved attention, memory and sleep, reduced the anxiety response to sirens. Academic stress reduced students' quality of life and learning results. To overcome the stress associated with the state of war in the country, a psychological support program was developed and applied, the purpose of which was to influence the psycho-physiological and psycho-emotional state, correction of maladaptive thoughts and beliefs, educational activities. The presence of academic stress in students of higher education institutions requires further development of pedagogical methods and psychological counseling to improve learning and psychological health of students.